IMPROVEMENT IMPACT RESISTANCE FOR FRONT AUTOMOTIVE BUMPER - Saeed Abu Alyazeed Albatlan (European Scientific Journal, ESJ, 2013)
Bumpers play an important role in preventing the impact energy from being transferred to the automobile and passengers. Saving the impact energy in the bumper to be released in the environment reduces the damages of the automobile and passengers. Therefore researchers have sought to make bumpers lighter without sacrificing strength, ability to absorb impact, or passenger safety. This study investigates the possibility of adding filling material between the bumper and front car body. The experimental tests were conducted and applied on front bumper of Fiat- Sahin vehicle.The results showed the improvement in bumper impact resistance about 260% when using one layer of honey comb cardboard cell and cardboard sheets as filling materials.